Gamma-Ray Dose From an Overhead Plume. Issue 5 (May 2017) - McNaughton, Michael W.; Gillis, Jessica M.; Ruedig, Elizabeth; Whicker, Jeffrey J.; Fuehne, David P.
Abstract : Abstract: Standard plume models can underestimate the gamma-ray dose when most of the radioactive material is above the heads of the receptors. Typically, a model is used to calculate the air concentration at the height of the receptor, and the dose is calculated by multiplying the air concentration by a concentration-to-dose conversion factor. Models indicate that if the plume is emitted from a stack during stable atmospheric conditions, the lower edges of the plume may not reach the ground, in which case both the ground-level concentration and the dose are usually reported as zero. However, in such cases, the dose from overhead gamma-emitting radionuclides may be substantial. Such underestimates could impact decision making in emergency situations. The Monte Carlo N-Particle code, MCNP, was used to calculate the overhead shine dose and to compare with standard plume models. At long distances and during unstable atmospheric conditions, the MCNP results agree with the standard models. At short distances, where many models calculate zero, the true dose (as modeled by MCNP) can be estimated with simple equations.